High reactivity of H2O vapor on GaN surfaces - Masatomo Sumiya; Masato Sumita; Yasutaka Tsuda; Tetsuya Sakamoto; Liwen Sang; Yoshitomo Harada; Akitaka Yoshigoe (Science and Technology of Advanced Materials)
Understanding the process of oxidation on the surface of GaN is important for improving metal-oxide-semiconductor (MOS) devices. Real-time X-ray photoelectron spectroscopy was used to observe the dynamic adsorption behavior of GaN surfaces upon irradiation of H2O, O2, N2O, and NO gases. It was found that H2O vapor has the highest reactivity on the surface despite its lower oxidation power. The adsorption behavior of H2O was explained by the density functional molecular dynamic calculation including the spin state of the surfaces. Two types of adsorbed H2O molecules were present on the (0001) (+c) surface: non-dissociatively adsorbed H2O (physisorption), and dissociatively adsorbed H2O (chemisorption) molecules that were dissociated with OH and H adsorbed on Ga atoms. H2O molecules attacked the back side of three-fold Ga atoms on the (0001̅) (−c) GaN surface, and the bond length between the Ga and N was broken. The chemisorption on the (101̅0) m-plane of GaN, which is the channel of a trench-type GaN MOS power transistor, was dominant, and a stable Ga-O bond was formed due to the elongated bond length of Ga on the surface. In the atomic layer deposition process of the Al2O3 layer using H2O vapor, the reactions caused at the interface were more remarkable for p-GaN. If unintentional oxidation can be resulted in the generation of the defects at the MOS interface, these results suggest that oxidant gases other than H2O and O2 should be used to avoid uncontrollable oxidation on GaN surfaces.